Genome-scale CRISPR screening at high sensitivity with an empirically designed sgRNA library - Henkel, Luisa; Rauscher, Benedikt; Schmitt, Barbara; Winter, Jan; Boutros, Michael (BMC biology, 2020)
In recent years, large-scale genetic screens using the CRISPR/Cas9 system have emerged as scalable approaches able to interrogate gene function with unprecedented efficiency and specificity in various biological contexts. By this means, functional dependencies on both the protein-coding and noncoding genome of numerous cell types in different organisms have been interrogated. However, screening designs vary greatly and criteria for optimal experimental implementation and library composition are still emerging. Given their broad utility in functionally annotating genomes, the application and interpretation of genome-scale CRISPR screens would greatly benefit from consistent and optimal design criteria.
Gesehen am 20.11.2023